Persistence and Corresponding Time Scales of Soil Moisture Dynamics During Summer in the Babao River Basin, Northwest China. Issue 17 (2nd September 2018) - shen, Shi; Ye, Sijing; Cheng, Changxiu; Song, Changqing; Gao, Jianbo; Yang, Jing; Ning, Lixin; Su, Kai; Zhang, Ting
Abstract: Soil moisture (SM) is an essential Earth surface and climate system variable. Insights into its persistence and corresponding time scales can improve numerical modeling and climate system prediction. In this study, SM from 17 observation stations within the Babao River Basin, Northwest China, between 1 June and 31 August 2014 were used to investigate persistence and corresponding time scales via adaptive fractal analysis. By conducting an adaptive fractal analysis of net radiation and by estimating the complementary cumulative distribution function of precipitation intervals, the relation between meteorological factors and the persistence and time scales of SM are determined and discussed. Results show that persistence and corresponding time scales of SM could be described using a three‐phase concept diagram. (1) At short time scales (approximately 0–14 hr [4 cm], 0–15 hr [10 cm], or 0–19 hr [20 cm]), the persistence of SM at most observation stations shows a strong long‐range correlation or nonstationarity. This phenomenon is essentially due to evaporation influenced by net radiation processes and the effects of rain. (2) At moderate time scales (approximately 14–159 hr [4 cm], 15–161 hr [10 cm], or 19–143 hr [20 cm]), the persistence of SM mostly exhibits a weak long‐range correlation or antipersistence due to net radiation process uncertainty and the probability of precipitation. (3) At long time scales (approximately greater than 159 hr [4 cm], 161 hr [10 cm], and 143 hr [20 cm]), the persistence of SM dynamics exhibits antipersistence because a high probability of precipitation reverses changes in the SM persistence. Key Points: The AFA method is used to analyze soil moisture persistence The persistence and corresponding time scales of soil moisture can be described using a three‐phase concept diagram Soil moisture persistence is influenced by net radiation and precipitation differently over these three phases